A Semiconductor‐Mediator‐Catalyst Artificial Photosynthetic System for Photoelectrochemical Water Oxidation. Issue 10 (3rd February 2022) - Niu, Fujun; Wang, Degao; Williams, Lenzi J.; Nayak, Animesh; Li, Fei; Chen, Xiangyan; Troian‐Gautier, Ludovic; Huang, Qing; Liu, Yanming; Brennaman, M. Kyle; Papanikolas, John M.; Guo, Liejin; et al.
Abstract: In fabricating an artificial photosynthesis (AP) electrode for water oxidation, we have devised a semiconductor‐mediator‐catalyst structure that mimics photosystem II (PSII). It is based on a surface layer of vertically grown nanorods of Fe2 O3 on fluorine doped tin oxide (FTO) electrodes with a carbazole mediator base and a Ru(II) carbene complex on a nanolayer of TiO2 as a water oxidation co‐catalyst. The resulting hybrid assembly, FTO|Fe2 O3 |−carbazole|TiO2 |−Ru(carbene), demonstrates an enhanced photoelectrochemical (PEC) water oxidation performance compared to an electrode without the added carbaozle base with an increase in photocurrent density of 2.2‐fold at 0.95 V vs. NHE and a negatively shifted onset potential of 500 mV. The enhanced PEC performance is attributable to carbazole mediator accelerated interfacial hole transfer from Fe2 O3 to the Ru(II) carbene co‐catalyst, with an improved effective surface area for the water oxidation reaction and reduced charge transfer resistance. Abstract : A hybrid semiconductor‐mediator‐catalyst photoelectrochemical (PEC) cell mimicking the PSII is proposed for efficient water oxidation. Addition of carbazole mediator results in a significant enhancement in PEC water oxidation performance as it promotes interfacial hole transfer from the Fe2 O3 light absorber to the Ru(carbene) catalyst, a function similar to the tyrosine residue in photosystem II. Such a semiconductor‐mediator‐catalyst assembly greatly inspires the rational design of high‐performance artificial photosynthesis systems.